Requirements of Digital Management as a Planning Decision-Taking Approach in Social Work Education Institutions - Balih, Mukhles Ramadan Mohamed; El Desouky, Hanan Zakaria El Sayed (جامعة بني سويف - كلية الخدمة الاجتماعية التنموية, 2022)
Information and communication technology was nowadays an integral part of everyday life And after the modern era witnessed changes in various aspects of human life, and the tremendous technological developments and the advancement of means of communication and information technology played a prominent role in these changes, and with the advent of the Internet, and the tremendous expansion in the use of digital networks in all fields, this led to a shift from traditional methods of accomplishing Business to digital methods in the completion of administrative work. The study seeks to achieve the following aims: 1- Determining the requirements for using digital management in planning decision-taking in social work education institutions. 2- Identifying obstacles to the use of digital management in planning decisiontaking in social work education institutions. 3- Introducing a suggested planning vision to activate the use of digital management in planning decision-taking in social work education institutions. The study attempts to answer the following questions: 1- What are the requirements for using digital management in planning decision-taking in social work education institutions? 2- What are the obstacles of using digital management in planning decisiontaking in social work education institutions? 3- What is the proposed or suggested planning vision to activate the use of digital management in planning decision-taking in social work education institutions? Also, the study attempts to test the validity of the following main hypothesis: It is expected that the requirements of digital management in planning decisiontaking in social work education institutions will be medium.” Study results: answering the study's questions, and the validity of the main hypothesis of the study was proven.
Keywords: التخطيط الاجتماعي -- الإدارة الرقمية -- الأعمال الإدارية -- التكنولوجيا الرقمية